Understanding Customer Loyalty in the Age of Value: A Study on Malaysian Consumers - Teo, Maybelline Kiat Hui (2007)
The competitive environment today has resulted in proliferation of choices offered to consumers, rendering the traditional marketing strategy questionable. Consequently, value-based management has become the hot topic by firms, integrating customer value into operations throughout the entire value chain. It has been widely researched that customer value is an important source of competitive edge for firms to be successful as they are able to generate customer loyalty to increase their share of sales and market. However, the fundamental issues on interdependency of customer value and loyalty have not been researched so far, to the best knowledge of the author. It is still not clear how strong loyalty prevails according to customer value when consumers are faced with so many choices in today’s competitive environment. If customer value is of paramount to consumers, will their loyalty towards certain brands hold? The present paper aims at making a contribution to marketing management to understand customer loyalty in the age of value. It seeks to identify and understand the interaction between customer value and loyalty, and to what extent loyalty exists when customers are presented with so many options offering customer value. This exploratory research in the context of Malaysian consumers contributes to marketers in creating and sustaining customer loyalty by understanding whether drivers for customer value are different for every consumer and to what extent these drivers influence them.